SPORTS TRAINING EQUIPMENT (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article was created to increase the knowledge about "Sports training equipment" and to study the various physical exercises that are formed taking into account the characteristics of these selected sports. Physical exercises are the main means of physical education, and information about them is given.